Use of appositive constructions in narrative creations by students on the Island of Gran Canaria - Hawach Umpiérrez, Anwar (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This article presents the results of a study carried out on the island of Gran Canaria (Spain), which aims to analyze syntactic maturity in students in the sixth year of Primary School, fourth year of Secondary School and second year of Bachillerato. Following the indexes proposed by K. Hunt, this article focuses on the use of appositions by students in the last years of each stage of the educational system and their possible relationships with the variables gender and age. A quantitative descriptive statistics approach was used to analyze the data. The results of the research allowed us to corroborate the existence of an associative relationship only between the age of the respondents and the use of appositive structures, since the sex variable was not significant in such use.
Keywords: syntactic maturity; sociolinguistics; appositions; social variables